2019
DOI: 10.3389/fnmol.2019.00162
|View full text |Cite
|
Sign up to set email alerts
|

Targeting GABAAR-Associated Proteins: New Modulators, Labels and Concepts

Abstract: γ-aminobutyric acid type A receptors (GABA A Rs) are the major mediators of synaptic inhibition in the brain. Aberrant GABA A R activity or regulation is observed in various neurodevelopmental disorders, neurodegenerative diseases and mental illnesses, including epilepsy, Alzheimer’s and schizophrenia. Benzodiazepines, anesthetics and other pharmaceutics targeting these receptors find broad clinical use, but their inherent lack of receptor subtype specificity cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 115 publications
0
19
0
Order By: Relevance
“…Although a majority of compounds have been developed that target the pore-forming subunits of GABA A Rs, recent advances in the field of GABA A R biology have illuminated that native GABA A R exist as a complex with other accessory proteins rather than in isolation ( Khayenko and Maric, 2019 ). Within the past decade ( Figure 1 ), novel transmembrane proteins have been discovered that associate with native GABA A Rs and have distinct effects on receptor trafficking, kinetics, and/or pharmacology (see Han et al, 2020 for an in-depth review).…”
Section: Recent Advances In Gaba a R Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although a majority of compounds have been developed that target the pore-forming subunits of GABA A Rs, recent advances in the field of GABA A R biology have illuminated that native GABA A R exist as a complex with other accessory proteins rather than in isolation ( Khayenko and Maric, 2019 ). Within the past decade ( Figure 1 ), novel transmembrane proteins have been discovered that associate with native GABA A Rs and have distinct effects on receptor trafficking, kinetics, and/or pharmacology (see Han et al, 2020 for an in-depth review).…”
Section: Recent Advances In Gaba a R Biologymentioning
confidence: 99%
“…In addition to GABA A R-associated scaffolds and molecular adaptor proteins ( Khayenko and Maric, 2019 ), newly identified transmembrane proteins that interact with GABA A Rs are additional targets that can potentially be exploited in drug development. In fact, transmembrane AMPAR regulatory proteins (TARPs), which are auxiliary subunits of AMPA receptors ( Ziff, 2007 ; Milstein and Nicoll, 2008 ), are currently being evaluated for the treatment of epilepsy and pain ( Maher et al, 2017 ).…”
Section: Recent Advances In Gaba a R Biologymentioning
confidence: 99%
“…Previous studies suggest the glutamatergic and GABAergic neurons and their neurotransmitter systems play crucial roles in the pathophysiology of schizophrenia 12 ; but, currently, there are no relevant new medications available for clinical use. GABA A receptors are heteropentameric structures assembled from a large family of subunits including two α (α1-6), two β (β1-3), and either one γ (γ1-3) or one δ subunit 15 .…”
Section: Discussionmentioning
confidence: 99%
“…γ-aminobutyric acid type A receptors (GABA A R) are a family of ligand-gated ion channels essential for the regulation of synaptic inhibition in the brain 10 . Aberrant GABA A R activities or dysregulation thereof are associated with various neurodevelopmental disorders, neurodegenerative diseases and psychiatric diseases, including autism, Alzheimer's, depression and schizophrenia 11,12 . With growing studies on γaminobutyric acid type A (GABA A ) receptors (GABA A R) accessory proteins and the molecules modulating receptor signaling in the central nervous system, targeting GABA A R and associated proteins might shed a light to novel therapeutic development for psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%
“…NL2 peptide (AEGEFIHNRYNRFFYWYGDPAK) is a tumor‐targeting peptide that was first synthesized by the T7 phage library A 24 . Also, previous studies have shown that NL2 peptide has good stability and tumor targeting activity with a specific diagnosis of HER2 tumor marker without toxicity 25,26 . Human epidermal growth factor receptor 2 (HER2) is known as a tumor marker that is overexpressed on more than 30% of breast cancers (HER2, c‐erbB2) B .…”
Section: Introductionmentioning
confidence: 99%